Pelatihan dan Pemanfaatan Minuman Herbal Teh Hijau sebagai Upaya Meningkatkan Imunitas Tubuh di Desa Sindangsari dan Talagasari Kecamatan Ciamis: Training and Utilization of Green Tea Herbal Beverage as an Effort to Enhance Body Immunity in Sindangsari and Talagasari Villages, Ciamis Subdistrict - Kusmiyati, Mimin; Sudaryat, Yayat; Herdiana, Irfan; Widyastuti, Tri; Fatimah, Cucu (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Green tea contains polyphenol and flavonoid compounds which have many benefits such as antioxidants, anti-inflammatory and antibacterial. Even though it is known that tea has various benefits, the level of public knowledge regarding this is still low. So this training aims to increase public awareness about the benefits of green tea. The training and evaluation methods used were post-test and pre-test by providing training on making and using green tea herbal drinks. Based on the results of the training, there was an increase in public knowledge of 15% after the training, which shows the effectiveness of training as an effective tool in increasing public understanding and knowledge regarding the benefits of green tea herbal drinks.